Molecular Characterization of Cryptosporidium Species in Children with Diarrhea in North West of Iran - Mahdavi Poor, Behroz (Int J Mol Cell Med, 2015)
Cryptosporidium is one of the most common causes of childhood diarrhea in developing countries. The aim of this randomized pilot study was to detect and characterize infective species and determine the genotypes of Cryptosporidium parasites in pediatric patients suffering from diarrhea in North West of Iran. A total of 113 fecal samples were collected from diarrheic children hospitalized in Tabriz Pediatric Hospital. The amplification of small subunit ribosomal RNA gene was performed using a nested polymerase chain reaction protocol and its products were digested using two restriction enzymes for Cryptosporidium species and genotype differentiation. Cryptosporidium oocysts were found in 2 (1.76%) children with diarrhea and restriction pattern revealed the presence of C.parvum bovine genotype in both positive fecal samples. The findings indicate that Cryptosporidium parvum is responsible for cryptosporidiosis in children in the study region and probably zoonotic transmission is the predominant route of parasite transmission.